Kualitas Karkas Ayam Broiler Yang Diberi Ransum Mengandung Ampas Tahu - Siti Dharmawati; Nordiansyah Firahmi; Nurul Wahdah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
The research aim to knowed the Influence Varying Degrees of Tofu Waste in the Broiler Carcass Quality Rasion. The research by the used ng 80 broilers Strain CP 707 in 5 treatments which each treatment consist of 4 replications, which in every replication consist of 4 broilers. Rasion treatment consist of AT0 (Ration without Tofu Waste), AT10 (Ration 90% + Tofu Waste 10%), AT20 (Ration 80% + Tofu Waste 20%), AT30 (Ration 70% + Tofu Waste 30%) and AT40 (Ration 60% + Tofu Waste 40%). The observed variables is the value of pH, fat percentage and organoleptic test in the colours, textures and aromas. Methode of data analysis using the methode of spectrum analysis and kruskalwallis Complete Random Design Pattern (RAL), if there is a difference between the treatment continued with Duncan’s Multiple Range Test (DMRT).The result showed that the influence tofu waste the real effect to pH flash and the colour of the carcass, but it is not influenced to aromas, textures, and fat content of the broilers. The highest pH in ration contain tofu waste 40% (6,10) treatment while the lowest in control (5,40), treatment highest colour in ration contain tofu waste 10% (3,29) while the lowest in control (2,92) treatment , highest quality in ration contain tofu waste 30% (3,24) treatment while the lowest in control (3,01) treatment, highest texture in ration contain tofu waste 40% (3,69) treatment while lowest in ration contain tofu waste 30% (3,52), the highest carcass fat in control (1,03) treatment while the lowest in ration contain tofu waste 30% (0,90).